Struktury uzasadniania. Część III. Kontekstualizm - Ziobrowski, Jacek (Filozofia Nauki, 2018)
This paper is the last part of a series of three articles concerning the structure of justification. The author discusses contextualism regarding the structure of justification in the versions put forward by David Annis and Michael Williams. Williams explicitly contrasts his view with both foundationalist and coherentist theories. He gives a novel and valuable account of the system of beliefs and the structure of justification. Still, one can have doubts as to its normative dimension, i.e. as to whether it correctly shows what the structure of justification should be like from the epistemic point of view.